Unwrapping ancient Egypt - Riggs, Christina (Bloomsbury Academic, 2014)
"In ancient Egypt, wrapping sacred objects, including mummified bodies, in layers of cloth was a ritual that lay at the core of Egyptian society. Yet in the modern world, attention has focused instead on unwrapping all the careful arrangements of linen textiles the Egyptians had put in place.This book breaks new ground by looking at the significance of textile wrappings in ancient Egypt, and at the way their unwrapping has shaped the way we think about the Egyptian past. Wrapping mummified bodies and divine statues in linen reflected the cultural values attached to this textile, with implications for understanding gender, materiality and hierarchy in Egyptian society. Unwrapping mummies and statues similarly reflects the values attached to Egyptian antiquities in the West, where the colonial legacies of archaeology, egyptology and racial science still influence how Egypt appears in museums and the press.From the tomb of Tutankhamun to the Arab Spring, Unwrapping Ancient Egypt raises critical questions about the deep-seated fascination with this culture - and what that fascination says about our own"